Persepsi Masyarakat Terhadap Implikasi Ekonomi Pembangunan Pariwisata Kota Batu - Pramudita, Rheza Pratama (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study uses qualitative research paradigm that only simbiolycs interactionism is limited in scope into an economic center. The authors analyze and describe the implications of tourism development that occurs in Kota Batu to the welfare of the community around tourism. The analytical method used is a method of coding transcript of the interview, and pemkanaan interviews. Sources of primary data in this study is from two informants key informants that the communities involved in tourism activities and support from government informant Batu with supported data library of the City of Stone.The results obtained are that the high tourism activity affects the welfare of the people ofBatu which includes the economic, education, and health. Basically solid tourism activity will lead to the opening of new jobs and rising incomes. Because it is dominated by SMEs. This is because the needs of high tourer.Keywords: Tourism, Implications, Welfare, and Community